Transforming Captivity Narratives in Kevin Wilmott’s The Only Good Indian (2009) - Mielke, Laura L. (American Studies, 2016)
In this essay, I closely examine Kevin Willmott’s The Only Good Indian (2009), a post-modern filmic reflection on the Native boarding school experience, to think about how narrative forms associated with captivity of white subjects mutate in the context of institutional violence. In particular, I consider the film’s depiction of the boarding school experience in light of American Indian accounts of such; the film’s use of the gothic-horror genre to capture the trauma of the boarding school student; and the film’s interrogation of the Western genre in light of repressed histories of colonialism.